2009
DOI: 10.1038/jhg.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of inverted GSTM exons by an intron of primate GSTM5 gene

Abstract: The human GSTM gene family is composed of five gene members, GSTM1-5, and plays an important role in detoxification. In this study, the human GSTM5 gene was found to have a long inverted repeat (LIR) in intron 5. The LIR is able to form a stem-loop structure with a 31-bp stem and a 9-nt loop. The intronic LIR was also identified in other primates but not in non-primates. The human and chimpanzee LIRs had undergone compensating mutations that make the stem loop more stable, suggesting a functional role for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Over 100 recombinogenic LIRs were found in the human genome. Occasionally, one repeat of an LIR is located in an exon, exemplified by GSTM5 gene [10]. Involvement of an exon in the formation of a stem-loop structure would result in even more complicated gene structures by creating various alternative splicing patterns, which has not been fully acknowledged at present.…”
Section: Case Study Using a Human Genome Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…Over 100 recombinogenic LIRs were found in the human genome. Occasionally, one repeat of an LIR is located in an exon, exemplified by GSTM5 gene [10]. Involvement of an exon in the formation of a stem-loop structure would result in even more complicated gene structures by creating various alternative splicing patterns, which has not been fully acknowledged at present.…”
Section: Case Study Using a Human Genome Sequencementioning
confidence: 99%
“…The evolutionary significance of the LIRs in primates is still under hot debate. A previous study has identified primate-specific LIRs in long introns of the genes that are involved in development of nervous systems and detoxification in humans [10]. Some of them are suggested to be inducers of cancers [11], [12].…”
Section: Introductionmentioning
confidence: 99%